Evaluation of the root canal morphology variations of maxillary premolars using cone-beam computed tomography - Stanković Antonije; Popović Jelena; Daković-Bjelaković Marija; Stošić Nenad; Nikolić Marija; Mitić Aleksandar; Barac Radomir; Milovanović Aleksandra (Serbian Medical Society - Dental Section, Belgrade, 2023)
Introduction Maxillary premolars often undergo endodontic treatment, which requires detailed knowledge of their canal morphology. The aim of this study was to determine the most common number of roots of maxillary premolars by analyzing CBCT images, as well as to determine the most common root canal configuration in maxillary premolars in the population of Southeast Serbia using the new system for classifying root canal morphology by Ahmed et al. Material and methods 55 CBCT images of male and 63 CBCT images of female patients were analyzed, which included 223 maxillary first premolars and 207 maxillary second premolars. The analysis was performed in the program Galileos. The number of roots of these teeth was determined and the canal morphology was classified in relation to the gender and side of maxilla. Results The maxillary first premolars most often had two roots and configuration type 2 TNB1 P1 , while the most maxillary second premolars had one root and configuration type 1 TNB1 . No significant difference was observed in the number of roots and type of configuration between male and female, as well as between left and right sides. Conclusion The classification of the tooth canal system according to Ahmed et al. emphasizes the advantage of simultaneous classification of the number of roots and the number of canals. Although most premolars do not pose a problem for treatment, there have been registered canal configurations of maxillary premolars that can be a challenge for endodontic treatment. A detailed analysis of the canal configuration can be performed using CBCT.